Case report: EGFR fusion mutation combined with EGFR amplification responds to EGFR-TKI therapy - Wang, Zhulin; Huang, Chunyao; Fan, Wenbo; Sun, Shaowu; Li, Kaiyuan; Liu, Xu; Pu, Jiangtao; Zhang, Guoqing; Li, Xiangnan (Frontiers in Oncology, 2024)
Given their good antitumor effects, epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are standard first-line therapy for EGFR-sensitive mutations, including exon 19 deletions and exon 21 L858R mutations. EGFR fusion mutations and EGFR amplification are very rare in non-small cell lung cancer (NSCLC). We describe 2 patients with NSCLC harboring EGFR fusion mutations (EGFR-MACF1 and EGFR-GNAT3) combined with EGFR amplification. Both patients received EGFR-TKI treatment, and 1 of them showed an antitumor response.